2012
DOI: 10.1007/s12013-012-9459-6
|View full text |Cite
|
Sign up to set email alerts
|

Pore Formation in Lipid Bilayer Membranes made of Phosphatidylcholine and Cholesterol Followed by Means of Constant Current

Abstract: This paper describes the application of chronopotentiometry to lipid bilayer research. The experiments were performed on bilayer lipid membranes composed of phosphatidylcholine and cholesterol and formed using the painting technique. Chronopotentiometric (U = f(t)) measurements were used to determine the membrane capacitance, resistance, and breakdown voltage as well as pore conductance and diameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 53 publications
2
22
1
Order By: Relevance
“…The lowest value of R sp at -1.1 V of 10 4.8  cm 2 for the bilayer on Hg is somewhat lower than that recorded for lipid bilayers of > 10 5 [ 44] and 10 6 to 10 8 [45]  cm 2 and in this study this decreases exponentially by two orders of magnitude with increase in applied negative potential. The presence of electrolyte in the bilayer is confirmed by a finite increased permeability to Zn 2+ which increases with increase in applied negative potential.…”
Section: Discussioncontrasting
confidence: 68%
“…The lowest value of R sp at -1.1 V of 10 4.8  cm 2 for the bilayer on Hg is somewhat lower than that recorded for lipid bilayers of > 10 5 [ 44] and 10 6 to 10 8 [45]  cm 2 and in this study this decreases exponentially by two orders of magnitude with increase in applied negative potential. The presence of electrolyte in the bilayer is confirmed by a finite increased permeability to Zn 2+ which increases with increase in applied negative potential.…”
Section: Discussioncontrasting
confidence: 68%
“…Molecular dynamics simulations provide a view of one type of permeabilizing structure, the lipid electropore (Tieleman 2004; Gurtovenko and Vattulainen 2005; Tarek 2005; Böckmann et al 2008; Levine and Vernier 2010), consistent with experimental observations (Melikov et al 2001; Naumowicz and Figaszewski 2013; Koronkiwicz et al 2002) and continuum models (Zimmermann et al 1974; Abidor et al 1979; Chizmadzhev and Abidor 1980; Weaver and Chizmadzhev 1996). The formation of these nanometer-scale, conductive pores is initiated by the electric-field-stabilized intrusion of interfacial water into the membrane interior, which leads to the construction of energy-minimized water bridges across the lipid bilayer and the reorganization of the membrane phospholipids along the water columns to form the hydrophilic wall of the pore (Tokman et al 2013).…”
Section: Introductionsupporting
confidence: 75%
“…the voltage required to breakdown a bilayer: several experimental studies characterized the impact of cholesterol contents for instance on the electroporation of simple lipid bilayers. [32][33][34][35] Most of the authors reported its stabilizing effect, as was later also found in MD simulation studies. 31,36 Yet, this seems not to be a universal behavior: in the case of diphytanoyl-glycerophosphocholine (DPhPC), lipid of which the saturated hydrocarbon chains are functionalized with methyl groups, cholesterol was found to slightly decrease the electroporation threshold.…”
Section: Introductionmentioning
confidence: 59%